Analisis Pengukuran Kinerja pada Rumah Sakit "X" Palembang - Dewi Rina Komarawati (JURNAL MANAJEMEN DAN BISNIS SRIWIJAYA, 2011)
This research was conducted to determine how hospital performance is measured by Value for money is the efficiency, effectiveness and economy. Research conducted at Siti Khadijah Islamic Hospital Palembang. The data used in analyzing the problem is secondary data in the form of budget and actual revenue and expenditure hospitals, and medical record documents. While the analytical technique used is quantitative analysis technique, a method of analyzing a series of information is data in the form of numbers or information obtained from the results reported in comparison with the theory that supports the analysis of quantitative data with measurements of efficiency, effectiveness, and economical. After research conducted a few indicators that do not meet the standard, showing the performance of Siti Khadijah Islamic hospital in Palembang is not optimal. For that the hospital would expect to make best efforts to evacuate and follow up reports of health services to the community level to maximum, and more careful in planning and realizing the needs, facilities and infrastructure to be guided by regulations.Keywords : Performance measurement, value for money, efficiency, effectiveness and economy.